Dietary whey reduces energy intake and alters hypothalamic gene expression in obese phyto-oestrogen-deprived male rats - Andreoli, Maria Florencia (2016)
Removing dietary phyto-oestrogens in adult male rats causes obesity and diabetes. As whey proteins have been reported to reduce food intakeand improve glucose homoeostasis, we investigated whether they could attenuate susceptibility to obesity and diabetes due to phytooestrogendeprivation. To this end, thirty male Wistar rats were fed a high-phyto-oestrogen (HP) or a phyto-oestrogen-free (PF) diet for10 weeks; six rats from each group were killed. The remaining HP animals (six animals) continued receiving the HP diet for 6 weeks. Theremaining PF rats (twelve rats) were divided in two groups: one was given the PF diet and the other a variation of the PF diet plus wheyprotein (PF-W). Body weight, food intake and adipose tissue weights were recorded. Hypothalamic mRNA expressions of orexigenic(neuropeptide Y, agouti-related protein (AgRP)) and anorexigenic (pro-opiomelanocortin (POMC), cocaine-amphetamine-related transcript(CART)) neuropeptides were quantified by real-time PCR. Serum glucose, insulin and total thyroxine (T4), thyroid-stimulating hormone,testosterone and oestradiol were assessed. After 10 weeks of PF diet, increased body weight, adiposity and energy intake, with up-regulationof AgRP and down-regulation of POMC´, were observed. Longer treatment exacerbated these results, increased total T4 levels, reducedoestradiol levels and impaired glucose homoeostasis. PF-W reduced energy intake and increased POMC expression; however, body weightand adiposity remained unchanged. PF-W could not prevent the hormonal changes or the high circulating glucose levels induced by phytooestrogendeprivation, but reduced fasting insulin. These data demonstrate that, although 6 weeks of whey administration could not preventobesity in phyto-oestrogen-deprived rats, the reduction in energy intake and circulating insulin could be beneficial with longer treatments.